2006
DOI: 10.1111/j.1464-410x.2006.06352.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumour‐associated plasma DNA represents an independent and informative predictor of prostate cancer

Abstract: and prostate volume, the median prostate cancer plasma DNA concentration served as diagnostic threshold in uni-and multivariate logistic regression models. Multivariate models were subjected to 200 bootstraps for internal validation and to reduce over-fit bias. RESULTSSubgroups consisted of 142 men with clinically localized prostate cancer and 19 with BPH. The median plasma concentration of cell-free DNA was 267 ng/mL in men with BPH vs 709 ng/mL in men with prostate cancer. In univariate analyses, plasma DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 14 publications
0
80
1
2
Order By: Relevance
“…Although we found increased DNA concentrations in plasma of PCa patients compared with patients with benign lesions and healthy individuals (29 ), and specific associations between the rate of LOH and differentiation grade, LOH was an infrequent event on cellfree plasma DNA. Despite the use of similar plasmaand PCR-based techniques, published studies have shown a broad range of detection rates of LOH, with contradictory results using blood from other tumor patients (30 -34 ).…”
Section: Discussionmentioning
confidence: 75%
“…Although we found increased DNA concentrations in plasma of PCa patients compared with patients with benign lesions and healthy individuals (29 ), and specific associations between the rate of LOH and differentiation grade, LOH was an infrequent event on cellfree plasma DNA. Despite the use of similar plasmaand PCR-based techniques, published studies have shown a broad range of detection rates of LOH, with contradictory results using blood from other tumor patients (30 -34 ).…”
Section: Discussionmentioning
confidence: 75%
“…It is known that cancer patients have higher cfDNA levels than healthy donors, however, the overall concentration of cfDNA varies considerably in blood samples in both groups [19][20][21][22][23]. An average of 180 ng cfDNA per mL of blood has been measured in cancer patients, whereas healthy individuals carry about 30 ng of cfDNA per mL of blood [24].…”
Section: Defining Circulating Cell Free Dna and Approaches To Liquid mentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23] Despite the use of similar PCR-based techniques, the published studies showed a broad range of detection rates of LOH with contradictory results in lung, colorectal and breast cancer patients. 19,20,[24][25][26] Increased concentrations of extracellular DNA have been detected in the plasma from numerous cancer patients 15,27 including PCa patients [28][29][30][31] compared with the low amounts detected in the blood from healthy individuals. The origin of free DNA in blood and BM is still discussed, and it is supposed that free extracellular DNA, which is early released into the blood circulation during the formation of primary tumors, is derived from necrotic and apoptotic cells.…”
mentioning
confidence: 99%